(untitled) (Czech Journal of International Relations, 2000)
This paper offers a non-traditional perspective on European integration. In it, integration is conceived of as the transfer of national, domestic institutions onto the international level. The goal of the paper is to show that the transfer of institutions, i.e. their export and import, are not peculiar to the relationship between the European Union and candidate countries, but that they represent a universal element of international politics throughout the centuries, which has only taken on a new form within the European integration process that began at the end of World War II. To understand how such transfers of decision making occur, the paper utilizes a theoretical perspective that combines the realist theory of power with constructivist theories of identity and the nature of the international system. Depending on the distribution of power, the international system is either balanced or unbalanced. Identity is considered a dynamic element that drives the state to expand and project its national institutions abroad. The author believes it is possible to distinguish between a Westphalian and post-Westphalian international order. Thus the paper looks for connections between three variables: institutional identity, distribution of power and the international system. The article concentrates on three major ways in which a state can transfer its institutions abroad. Uninvited exports, targeting the domestic order of another state, are associated with unbalanced relations within the Westphalian system, while international exports, targeting the interstate level, are related to balanced relations within the Westphalian system. Supranational exports, targeting the supranational level, originate within balanced, post-Westphalian relationships – the author specifically mentions the European Coal and Steel Community – and they have become a defining feature of European integration. The replacement of international institutional exports with supranational ones is considered a decisive factor in the transition from the Westphalian to a post-Westphalian system. Institutional exports appear in connection with EU enlargement as well. These exports take place in a Westphalian context and represent the necessary conditions of entry for the present candidate countries into the post-Westphalian system.